Sirt1 and Sirt3 Activation Improved Cardiac Function of Diabetic Rats via Modulation of Mitochondrial Function - Paramesha, Bugga; Anwar, Mohammed Soheb; Meghwani, Himanshu; Maulik, Subir Kumar; Arava, Sudheer Kumar; Banerjee, Sanjay K (Antioxidants, 2021)
In the present study, we aimed to evaluate the effect of Sirt1, Sirt3 and combined activation in high fructose diet-induced insulin resistance rat heart and assessed the cardiac function focusing on mitochondrial health and function. We administered the Sirt1 activator; SRT1720 (5 mg/kg, i.p.), Sirt3 activator; Oroxylin-A (10 mg/kg i.p.) and the combination; SRT1720 + Oroxylin-A (5 mg/kg and 10 mg/kg i.p.) daily from 12th week to 20th weeks of study. We observed significant perturbations of most of the cardiac structural and functional parameters in high fructose diet-fed animals. Administration of SRT1720 and Oroxylin-A improved perturbed cardiac structural and functional parameters by decreasing insulin resistance, oxidative stress, and improving mitochondrial function by enhancing mitochondrial biogenesis, OXPHOS expression and activity in high fructose diet-induced insulin-resistant rats. However, we could not observe the synergistic effect of SRT1720 and Oroxylin-A combination. Similar to in-vivo study, perturbed mitochondrial function and oxidative stress observed in insulin-resistant H9c2 cells were improved after activation of Sirt1 and Sirt3. We observed that Sirt1 activation enhances Sirt3 expression and mitochondrial biogenesis, and the opposite effects were observed after Sirt1 inhibition in cardiomyoblast cells. Taken together our results conclude that activation of Sirt1 alone could be a potential therapeutic target for diabetes-associated cardiovascular complications.